PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS MODEL KOOPERATIF TIPE THINK PAIR SQUARE PADA MATERI SEGIEMPAT DAN SEGITIGA - Tania Afarisa (Jurnal Edukasi dan Penelitian Matematika, 2020)
This study aims to develop Student Worksheet (LKPD) based on the Think Pair Square type of cooperative model on rectangles and triangles material for students of class VII JHS which are valid and practical. This development research uses the Plomp model which consists of three stages, namely the Preliminary Research Phase, the Development or Prototyping Phase, and the Assessment Phase. Based on the results of data analysis, it shows that student worksheets based on the Think Pair Square type of cooperative model on the material of rectangles and triangles in terms of content feasibility, the Think Pair Square cooperative model, language, presentation and graphics have a validity level of 83.33% with a very valid category. LKPD also met the practical criteria from the results of the questionnaire responses of three students who had carried out the One-to-One Evaluation with a percentage of 91.48%. Based on these results, it can be concluded that the student worksheets based on the Think Pair Square type of cooperative model on the material of rectangles and triangles for grade VII junior high school students can be declared valid and practical. Keywords __Development Research, Student Worksheet, Think Pair Square